Waste recovery trolley of laser cutting machine - HE FUQIAN (2022)
The utility model discloses a laser cutting machine waste recycling trolley which comprises a main recycling trolley body, a secondary recycling trolley body is arranged on the front face of the main recycling trolley body, two U-shaped locking rings are connected to the front face of the main recycling trolley body and the front face of the secondary recycling trolley body, and two locking holes are formed in the back face of the secondary recycling trolley body. Movable lock rods are movably connected to the inner walls of the movable holes in a penetrating mode, the two movable lock rods are movably connected to the interior of the U-shaped lock ring in a penetrating mode, and springs are movably arranged outside the two movable lock rods. The U-shaped lock rod, the lock hole, the movable lock rod, the movable ring and the spring are arranged, the movable ring drives the movable lock rod to have downward force through the elastic action of the spring, and then the movable lock rod clamps the U-shaped lock